Method for preparing graphene-like nanosheets by magnesium metal assisted mixed salt and application of graphene-like nanosheets

Metal magnesium-assisted mixed salt activation prepares graphene-like nanosheets with high specific surface area and pore structure, addressing the limitations of potassium hydroxide-based methods and achieving superior electrochemical performance for supercapacitors.

CN119230305APending Publication Date: 2024-12-31WUHAN UNIV OF SCI & TECH +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411346086.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Existing methods for preparing porous carbon materials for supercapacitors using potassium hydroxide as an activator face issues such as alkali explosions and result in materials with low specific surface area and specific capacitance.

Method used

A method using metal magnesium-assisted mixed salt activation with potassium carbonate and sodium carbonate as activators to prepare graphene-like nanosheets, which are then used as electrode materials for supercapacitors.

Benefits of technology

The method produces graphene-like nanosheets with abundant growth, large specific surface area, and developed pore structure, resulting in high conductivity and excellent electrochemical performance, with specific capacitance up to 116F g-1 at 1A g-1 current density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230305A_ABST
    Figure CN119230305A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing graphene-like nanoparticles by using metal magnesium to assist mixed salt and application of the graphene-like nanoparticles. Cotton straw biomass carbon is used as a raw material, potassium carbonate and sodium carbonate are used as activators, gas carbon monoxide released in the heating process and alkaline earth metal potassium and sodium intervene in the activation process, then cross-linked sp3 carbon atoms in an amorphous carbon-containing precursor release graphite microcrystals, then the graphite microcrystals are recrystallized to form a graphene layer, and the graphene layer is formed. And finally, the graphene-like nanosheet is formed. According to the method, graphene-like nanosheets are prepared on the basis of mixed salt activation, and magnesium powder, potassium carbonate and sodium carbonate are added and mixed for co-activation on the basis. At high temperature, magnesium powder can promote decomposition of mixed salt, potassium and sodium in the salt can be released more quickly to react with biomass carbon, and formation of graphene-like nanosheets is promoted. The obtained graphene-like nanosheet has a relatively large specific surface area, and shows relatively high specific capacitance, excellent cycling stability and rate capability when being used as a supercapacitor electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of energy materials and provides a method for preparing graphene-like nanosheets by using metal magnesium-assisted mixed salt and application thereof. Background Art

[0002] With the energy crisis and environmental problems caused by the excessive consumption of fossil fuels becoming increasingly serious. In order to effectively utilize renewable energy, it is urgent to develop high-performance energy storage devices. At present, the most widely used and most mature chemical batteries are lithium batteries, but lithium batteries have disadvantages such as poor cycle life, environmental pollution and slow energy transmission. Compared with other types of energy storage devices such as batteries, supercapacitors have attracted widespread attention from researchers because of their advantages such as high safety, long life, fast charging speed, high power density and wide operating temperature range. Electrode materials, as an important component of supercapacitors, determine the performance of supercapacitors. Therefore, developing a supercapacitor electrode material with excellent performance is the most direct way to improve the performance of supercapacitors. Among them, porous carbon is the most widely studied supercapacitor electrode material due to its wide sources, low cost, environmental friendliness and diverse structures.

[0003] Biomass can still retain its original structure after thermal cracking to remove degradable components, and is an excellent precursor for preparing porous carbon materials. At present, biomass-based porous carbon is mainly obtained by chemical activation using strong alkali potassium hydroxide as an activator. Potassium hydroxide reacts violently during the activation process, resulting in an "alkali explosion" phenomenon, and the formed alkali vapor will also corrode the equipment. The patent document "Method and application of preparing three-dimensional porous graphene sheets using low-temperature double salt compounds (CN 113307254A)" discloses a method for preparing flower-shaped porous carbon with three-dimensional porous graphene-like sheets grown on the surface using biomass carbon as a raw material and potassium carbonate (K2CO3) and sodium carbonate (Na2CO3) as activators. This method avoids the problems caused by potassium hydroxide activation, but the porous carbon formed when it is applied to activate biomass carbon has a low specific surface area and specific capacitance.

[0004] Therefore, how to prepare a capacitive carbon material that has high specific surface area, high capacitance performance and is rich in graphene-like nanosheets is one of the research focuses in the field of capacitance. Summary of the invention

[0005] Based on the defects in the background technology, the present invention provides a method for preparing graphene-like nanosheets by metal magnesium-assisted mixed salt. Using alkaline earth metal magnesium as an auxiliary agent and mixed salt potassium carbonate and sodium carbonate as activators, graphene-like nanosheets are prepared by metal magnesium-assisted molten salt activation. Such graphene nanosheets have the advantages of abundant growth, large specific surface area, developed pore structure and high conductivity, so they show excellent electrochemical properties as supercapacitor electrode materials.

[0006] The technical solution of the present invention is as follows:

[0007] A method for preparing a graphene nanosheet capacitor carbon material using a magnesium-assisted mixed salt, characterized in that it comprises the following steps:

[0008] Step 1: Wash and dry the cotton straw raw material, place it in a tube furnace, pre-carbonize it under an argon or nitrogen atmosphere, and then crush it in a crusher to form powder;

[0009] Step 2: Mix the pre-carbonized material, metal magnesium and activator in a certain mass ratio of 1:0-1:0-10; wherein the molar ratio of the activator potassium carbonate to sodium carbonate is 0:1-1:0;

[0010] Step 3: placing the mixture obtained in step 2 in a tube furnace, performing an activation reaction under an argon or nitrogen atmosphere, and taking it out after cooling to room temperature;

[0011] Step 4: Wash the mixture obtained in step 3 with a dilute hydrochloric acid solution and deionized water until the solution becomes neutral;

[0012] Step 5: drying the product obtained in step 4 to obtain a biomass-based graphene nanosheet capacitor carbon material;

[0013] Step 6: The graphene-like nanosheets obtained in step 5 are used as electrode materials.

[0014] Preferably, the particle size of the cotton straw powder is less than 50 μm; the pre-carbonization temperature is 350-750°C, and the heating rate is 5-10°C min -1 , the pre-carbonization time is 3-5h.

[0015] Preferably, in step 2, the mass ratio of the pre-carbonized material to the activator is 1:1-1:10; the activator is potassium carbonate and sodium carbonate, the molar ratio of potassium carbonate to sodium carbonate is 0:1-1:0, and the mass ratio of the pre-carbonized material to metallic magnesium is 0:1-1:0.

[0016] Preferably, the activation temperature in step 3 is 600-1000°C, the activation reaction time is 5h, and the heating rate is 5°C min -1 .

[0017] Preferably, the concentration of hydrochloric acid in step 4 is 0.5-2 mol / L, and the stirring time is 5-10 h.

[0018] The present invention also discloses a biomass capacitor carbon material, which is prepared by the above-mentioned method of preparing a graphene nanosheet capacitor carbon material with the aid of metal magnesium mixed salt, and is characterized in that: the biomass capacitor carbon material includes a large number of micropores and mesopores, the micropore diameter distribution is about 2nm, and the mesopore diameter is about 5nm; at 1A g -1 At the current density, the discharge capacity is 116F g -1 .

[0019] The present invention also discloses a supercapacitor, which is characterized by comprising an electrode material, wherein the electrode material adopts the above-mentioned biomass capacitor carbon material.

[0020] The present invention also discloses a test method for testing the electrochemical performance of electrode materials, which is a test method for testing the above-mentioned biomass capacitor carbon material: the electrochemical performance test of the material is carried out using a three-electrode system, using a 6M KOH solution as an electrolyte, a platinum sheet electrode as a counter electrode, and saturated mercuric oxide as a reference electrode.

[0021] Beneficial Effects

[0022] 1. The graphene-like nanosheets prepared by the present invention are prepared from cotton straw as raw materials, and metal magnesium is used to assist mixed salt to prepare biomass-based graphene-like nanosheets. The method is simple, environmentally friendly and easy to industrialize, and avoids the violent reaction of alkaline activators during the activation process, resulting in "alkali explosion" and other phenomena.

[0023] 2. The graphene-like nanosheets prepared by the present invention have the following characteristics: after the introduction of metallic magnesium, the graphene-like nanosheets grow abundantly in the structure; the abundant graphene-like nanosheets provide a large specific surface area and good conductivity, and the abundant pore structure is conducive to the contact of the electrolyte; the three-dimensional network formed by the interconnection between the abundant graphene-like nanosheets provides a fast ion and electron transfer rate; the above advantages together provide the graphene-like nanosheets with an excellent electrochemical performance.

[0024] 3. The graphene-like nanosheets prepared in the present invention are used as capacitor carbon electrode materials. In 6M KOH electrolyte, 1A g -1 At this current density, its specific capacitance reaches 116F g -1 ; at 10A g -1 At this current density, the specific capacitance remains at 87 F g -1 , showing high capacity and good rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a scanning electron microscope image of the capacitor carbon material prepared in Example 1;

[0026] Figure 2is a transmission electron microscope image of the capacitor carbon material prepared in Example 1;

[0027] Figure 3 is the X-ray diffraction pattern of the capacitor carbon material prepared in Example 1;

[0028] Figure 4 is the Raman graph of the capacitive carbon material prepared in Example 1;

[0029] Figure 5 is the BET diagram of the capacitive carbon material prepared in Example 1;

[0030] Figure 6 is a pore size distribution diagram of the capacitor carbon material prepared in Example 1;

[0031] Figure 7 Thermogravimetric diagram of the capacitive carbon material prepared in Example 1;

[0032] Figure 8 The thermogravimetric-mass spectrum of the capacitive carbon material prepared in Example 1;

[0033] Fig. 9 This is a diagram of the electrochemical performance of the capacitive carbon material prepared in Example 1. DETAILED DESCRIPTION

[0034] The present invention uses cotton stalks as raw materials, metal magnesium as an auxiliary agent, and mixed salt (K2CO3 and Na2CO3) as an activator to prepare graphene-like nanosheets through a metal magnesium-assisted molten salt activation method.

[0035] The present invention selects cotton stalk straw as raw material because of its advantages such as low cost, good porosity, and stable physical and chemical properties. The lignin in the internal structure is converted into a carbon skeleton at high temperature to avoid complete collapse after carbonization. The cellulose reacts with the gas released during the pyrolysis-carbonization process to produce developed pores, which provide high capacitance, good stability and cyclability for the electrode material.

[0036] The graphene-like nanosheets prepared by the present invention have the advantages of abundant growth, large specific surface area, developed pore structure and high conductivity, and can be used as electrode materials for supercapacitors.

[0037] The present invention provides a method for preparing a graphene nanosheet capacitor carbon material by using a magnesium-assisted mixed salt, comprising the following steps:

[0038] (1) Wash and dry the cotton straw raw materials, and then pre-carbonize them at 580°C with a heating rate of 5°C min -1 , pre-carbonization time 3h, crushed in a crusher into powder;

[0039] (2) taking a certain mass of crushed pre-carbonized material precursor and mixing it evenly with metal magnesium, K2CO3 and Na2CO3 in a mass ratio of 1:0-1:0-10, wherein the molar ratio of the activator is 0:1-1:0;

[0040] (3) placing the mixture obtained in step 2 in a tube furnace, heating it to 600-1000° C. in an argon or nitrogen atmosphere for activation reaction, and taking it out after cooling to room temperature;

[0041] (4) washing the mixture obtained in step 3 with a dilute hydrochloric acid solution and deionized water until the solution becomes neutral;

[0042] (5) drying the product obtained in step 4 to obtain the graphene-like nanosheets;

[0043] (6) Using the graphene-like nanosheets obtained in step 5 as electrode materials. Mix the prepared capacitive carbon material, acetylene black, and binder (polytetrafluoroethylene) in a mass ratio of 8:1:1, roll them into sheets, and dry them in a vacuum drying oven;

[0044] (7) The electrochemical performance test of the obtained material was carried out using a three-electrode system, with 6M KOH solution as the electrolyte, platinum sheet as the counter electrode, and saturated mercuric oxide as the reference electrode. The electrochemical test was carried out using a Chenhua electrochemical workstation. The cyclic voltammetry test was set up with a voltage range of -1.0 V to 0 V and a scan rate of 50 mV s -1 ; Impedance test setting, frequency range is 1000KHz-0.1Hz, voltage is initial voltage; Constant current charge and discharge performance test setting, voltage range is -1.0V to 0V, current density is 1A g -1 .

[0045] Example 1

[0046] (1) 1 kg of cotton straw raw material was washed and dried, and then pre-carbonized at 580 °C with a heating rate of 5 °C min -1 , after pre-carbonization for 3 hours, crush it in a crusher to become powder;

[0047] (2) mixing the powdered raw material with the magnesium powder auxiliary agent and the activator (K2CO3 and Na2CO3) in a mass ratio of 1:0.3:4, wherein the molar ratio of K2CO3 and Na2CO3 is 0:1-1:0, and the masses are 1 g of the powdered raw material, 0.3 g of magnesium powder, 2.04 g of potassium carbonate and 1.96 g of sodium carbonate respectively;

[0048] (3) Place the mixture obtained in step 2 in a tube furnace and heat it to 900°C in an argon or nitrogen atmosphere for activation reaction. The activation time is 5 h, and the heating rate is 5°C min -1 , take out after cooling to room temperature;

[0049] (4) The mixture obtained in step 3 is washed with 2 mol / L HCl solution and deionized water until the solution is neutral;

[0050] (5) Drying the obtained carbon in a freeze dryer for 12 h yields graphene-like nanosheet capacitor carbon.

[0051] (6) The graphene-like nanosheets obtained in step 5 are used as electrode materials. The prepared capacitor carbon material, acetylene black, and binder (polytetrafluoroethylene) are mixed in a mass ratio of 8:1:1 and rolled into sheets, with the specific mass being 80 mg of capacitor carbon material, 10 mg of acetylene black, and 10 mg of binder, and then placed in a vacuum drying oven for drying;

[0052] (7) The electrochemical performance test of the obtained material was carried out using a three-electrode system, with 6M KOH solution as the electrolyte, platinum sheet as the counter electrode, and saturated mercuric oxide as the reference electrode. The electrochemical test was carried out using a Chenhua electrochemical workstation. The cyclic voltammetry test was set up with a voltage range of -1.0 V to 0 V and a scan rate of 50 mV s -1 ; Impedance test setting, frequency range is 1000KHz-0.1Hz, voltage is initial voltage; Constant current charge and discharge performance test setting, voltage range is -1.0V to 0V, current density is 1A g -1 .

[0053] The capacitor carbon material obtained by Example 1 is shown in the accompanying drawings, wherein: Figure 1 The SEM image of the product after adding Mg for activation is shown in Figure 1. As can be seen from the image, the surface of the prepared capacitive carbon material is rich in a large number of graphene-like nanosheets with consistent length and uniform distribution.

[0054] Figure 2 This is a transmission electron microscope image of the product after adding Mg activation. It can be seen from the image that the graphene-like nanosheets are cross-stacked on the surface of the capacitor carbon material to form a cross-linked three-dimensional structure;

[0055] Figure 3 is the X-ray diffraction spectrum of the activated product. It can be seen from the figure that the peak of the (002) crystal plane in the XRD spectrum after adding Mg is significantly higher than that without adding Mg, and the graphitization intensity is significantly increased;

[0056] Figure 4 From the Raman spectrum, it can be seen that after adding Mg, the corresponding D band peak intensity decreases, and the corresponding G band peak intensity increases, resulting in a decrease in its defect level and a significant increase in the degree of graphitization, which is consistent with XRD.

[0057] Figure 5 , 6The nitrogen adsorption-desorption curve and pore size distribution diagram of the activated product. It can be seen from the figure that the adsorption amount in the front section after adding Mg is significantly higher than that without adding Mg. At the same time, the number of micro-mesopores around 0-2nm and 5nm increases exponentially, and the corresponding specific surface area also increases significantly.

[0058] Figure 7 This is the thermogravimetric curve during the activation process. It can be seen from the figure that products are generated between 600-700°C. The substance is MgO, which acts as a template to regulate the micro-mesopore ratio of carbon to achieve high specific surface area and good electrochemical performance.

[0059] Figure 8 is the mass spectrometry curve during the activation process. It can be seen from the figure that after adding magnesium powder, H2O is significantly reduced at low temperature, and more H2 and CO are produced instead, which enhances the activation-catalytic effect of the mixed salt and enables it to grow more graphene-like nanosheets; in the higher temperature range, the CH4 and CO2 curves have obvious peaks at 600-700℃, which is consistent with the formation of MgO in thermogravimetry; ultimately, metallic magnesium forms more porous structures in the form of MgO as a template.

[0060] Fig. 9 The three-electrode constant current charge-discharge curve of the prepared capacitive carbon material. In 6M KOH solution, 1A g -1 At a current density of 116F g -1 High specific capacitance.

[0061] The surface of the capacitor carbon electrode material prepared in Example 1 has abundant graphene-like nanosheets, providing the largest specific surface area and good conductivity, rich pore structure, and more comprehensive contact with the electrolyte; and the electrochemical performance provided is optimal.

[0062] Comparative Example

[0063] (1) 1 kg of cotton straw raw material was washed and dried, and then pre-carbonized at 580 °C with a heating rate of 5 °C min -1 , pre-carbonization time 3h. Then put it in a crusher and crush it into powder;

[0064] (2) mixing the powdered raw material, magnesium powder and activator (K2CO3, Na2CO3) in a mass ratio of 1:0:4, wherein the molar ratio of K2CO3 to Na2CO3 is 0.45:0.55, and the masses are 1 g of powdered raw material, 0 g of magnesium powder, 2.04 g of potassium carbonate and 1.96 g of sodium carbonate respectively;

[0065] (3) Place the mixture obtained in step 2 in a tube furnace and heat it to 900°C in an argon or nitrogen atmosphere for activation reaction. The activation time is 5 h, and the heating rate is 5°C min -1, take out after cooling to room temperature;

[0066] (4) The mixture obtained in step 3 is washed with 2 mol / L HCl solution and deionized water until the solution is neutral;

[0067] (5) Drying the obtained carbon in a freeze dryer for 12 h yields graphene-like nanosheet capacitor carbon.

[0068] (6) The graphene-like nanosheets obtained in step 5 are used as electrode materials. The prepared capacitor carbon material, acetylene black, and binder (polytetrafluoroethylene) are mixed in a mass ratio of 8:1:1 and rolled into sheets, with the specific mass being 80 mg of capacitor carbon material, 10 mg of acetylene black, and 10 mg of binder, and then placed in a vacuum drying oven for drying;

[0069] The three-electrode constant current charge-discharge curve of the prepared capacitive carbon material was 1A g -1 At a current density of 42F g -1 The specific capacitance of the capacitor carbon obtained by the above-mentioned embodiment is analyzed and it is known that the graphene-like nanosheets on the surface of the capacitor carbon material obtained by double salt activation alone grow sparsely and the specific capacitance is very low.

[0070] By analyzing the above comparative examples, it can be seen that without the assistance of metal magnesium, the grown graphene-like nanosheets are smaller, shorter, have an underdeveloped pore structure, a smaller specific surface area, and exhibit a lower specific capacitance.

[0071] Example 2

[0072] (1) 1 kg of cotton straw raw material was washed and dried, and then pre-carbonized at 580 °C with a heating rate of 5 °C min -1 , pre-carbonization time 3h. Then put it in a crusher and crush it into powder;

[0073] (2) mixing the powdered raw material with magnesium powder and an activator (K2CO3, Na2CO3) in a mass ratio of 1:0.2:4, wherein the molar ratio of K2CO3 to Na2CO3 is 0:1-1:0, and the masses are 1 g of the powdered raw material, 0.2 g of magnesium powder, 2.04 g of potassium carbonate and 1.96 g of sodium carbonate respectively;

[0074] (3) Place the mixture obtained in step 2 in a tube furnace and heat it to 900°C in an argon or nitrogen atmosphere for activation reaction. The activation time is 5 h, and the heating rate is 5°C min -1 , take out after cooling to room temperature;

[0075] (4) The mixture obtained in step 3 is washed with 2 mol / L HCl solution and deionized water until the solution is neutral;

[0076] (5) Drying the obtained carbon in a freeze dryer for 12 h yields graphene-like nanosheet capacitor carbon.

[0077] (6) The graphene-like nanosheets obtained in step 5 are used as electrode materials. The prepared capacitor carbon material, acetylene black, and binder (polytetrafluoroethylene) are mixed in a mass ratio of 8:1:1 and rolled into sheets, with the specific mass being 80 mg of capacitor carbon material, 10 mg of acetylene black, and 10 mg of binder, and then placed in a vacuum drying oven for drying;

[0078] The three-electrode constant current charge-discharge curve of the prepared capacitive carbon material was 1A g -1 At a current density of 105F g -1 High specific capacitance.

[0079] The analysis of the capacitor carbon obtained in the above examples shows that a lower amount of magnesium powder has no obvious effect on promoting the mixed salt activation process.

[0080] Example 3

[0081] (1) 1 kg of cotton straw raw material was washed and dried, and then pre-carbonized at 580 °C with a heating rate of 5 °C min -1 , pre-carbonization time 3h. Then put it in a crusher and crush it into powder;

[0082] (2) mixing the powdered raw material, magnesium powder and activator (K2CO3, Na2CO3) in a mass ratio of 1:0.4:4, wherein the molar ratio of K2CO3 to Na2CO3 is 0:1-1:0, and the masses are 1 g of powdered raw material, 0.4 g of magnesium powder, 2.04 g of potassium carbonate and 1.96 g of sodium carbonate respectively;

[0083] (3) Place the mixture obtained in step 2 in a tube furnace and heat it to 900°C in an argon or nitrogen atmosphere for activation reaction. The activation time is 5 h, and the heating rate is 5°C min -1 , take out after cooling to room temperature;

[0084] (4) The mixture obtained in step 3 is washed with 2 mol / L HCl solution and deionized water until the solution is neutral;

[0085] (5) Drying the obtained carbon in a freeze dryer for 12 h yields graphene-like nanosheet capacitor carbon.

[0086] (6) The graphene-like nanosheets obtained in step 5 are used as electrode materials. The prepared capacitor carbon material, acetylene black, and binder (polytetrafluoroethylene) are mixed in a mass ratio of 8:1:1 and rolled into sheets, with the specific mass being 80 mg of capacitor carbon material, 10 mg of acetylene black, and 10 mg of binder, and then placed in a vacuum drying oven for drying;

[0087] The three-electrode constant current charge-discharge curve of the prepared capacitive carbon material was 1A g -1 At a current density of 101F g -1 High specific capacitance.

[0088] The analysis of the capacitor carbon obtained by the above examples shows that: excessive magnesium powder dosage inhibits the activation process of the mixed salt.

[0089] Example 4

[0090] (1) 1 kg of cotton straw raw material was washed and dried, and then pre-carbonized at 580 °C with a heating rate of 5 °C min -1 , pre-carbonization time 3h. Then put it in a crusher and crush it into powder;

[0091] (2) mixing the powdered raw material with magnesium powder and an activator (K2CO3, Na2CO3) in a mass ratio of 1:0.3:4, wherein the molar ratio of K2CO3 to Na2CO3 is 0:1-1:0, and the masses are 1 g of the powdered raw material, 0.3 g of magnesium powder, 2.04 g of potassium carbonate and 1.96 g of sodium carbonate, respectively;

[0092] (3) Place the mixture obtained in step 2 in a tube furnace and heat it to 800°C in an argon or nitrogen atmosphere for activation reaction. The activation time is 5 h, and the heating rate is 5°C min -1 , take out after cooling to room temperature;

[0093] (4) The mixture obtained in step 3 is washed with 2 mol / L HCl solution and deionized water until the solution is neutral;

[0094] (5) Drying the obtained carbon in a freeze dryer for 12 h yields graphene-like nanosheet capacitor carbon.

[0095] (6) The graphene-like nanosheets obtained in step 5 are used as electrode materials. The prepared capacitor carbon material, acetylene black, and binder (polytetrafluoroethylene) are mixed in a mass ratio of 8:1:1 and rolled into sheets, with the specific mass being 80 mg of capacitor carbon material, 10 mg of acetylene black, and 10 mg of binder, and then placed in a vacuum drying oven for drying;

[0096] The three-electrode constant current charge-discharge curve of the prepared capacitive carbon material was 1A g -1 At a current density of 56F g -1 Specific capacitance.

[0097] Through the analysis of the above examples, it can be seen that although metal magnesium is introduced, the catalytic activation at a lower temperature still cannot grow good graphene-like nanosheets, and only has a lower specific capacitance. This shows that the reaction temperature is also an important condition affecting the growth of graphene-like nanosheets. Only at a suitable temperature can the auxiliary effect of metal magnesium be better exerted.

[0098] Example 5

[0099] (1) 1 kg of cotton straw raw material was washed and dried, and then pre-carbonized at 580 °C with a heating rate of 5 °C min -1 , pre-carbonization time 3h. Then put it in a crusher and crush it into powder;

[0100] (2) mixing the powdered raw material with magnesium powder and an activator (K2CO3, Na2CO3) in a mass ratio of 1:0.3:4, wherein the molar ratio of K2CO3 to Na2CO3 is 0:1-1:0, and the masses are 1 g of the powdered raw material, 0.3 g of magnesium powder, 2.04 g of potassium carbonate and 1.96 g of sodium carbonate, respectively;

[0101] (3) Place the mixture obtained in step 2 in a tube furnace and heat it to 1000°C in an argon or nitrogen atmosphere for activation reaction. The activation time is 5 h, and the heating rate is 5°C min -1 , take out after cooling to room temperature;

[0102] (4) The mixture obtained in step 3 is washed with 2 mol / L HCl solution and deionized water until the solution is neutral;

[0103] (5) Drying the obtained carbon in a freeze dryer for 12 h yields graphene-like nanosheet capacitor carbon.

[0104] (6) The graphene-like nanosheets obtained in step 5 are used as electrode materials. The prepared capacitor carbon material, acetylene black, and binder (polytetrafluoroethylene) are mixed in a mass ratio of 8:1:1 and rolled into sheets, with the specific mass being 80 mg of capacitor carbon material, 10 mg of acetylene black, and 10 mg of binder, and then placed in a vacuum drying oven for drying;

[0105] The three-electrode constant current charge-discharge curve of the prepared capacitive carbon material was 1A g -1 At a current density of 68F g -1 Specific capacitance.

[0106] By analyzing the above examples, it can be seen that although catalysis-activation at a higher temperature can grow better graphene-like nanosheets, it still has only a lower specific capacitance. This is attributed to the fact that at a higher temperature, there are fewer pore structures, the specific surface area is reduced, and the active sites are reduced. Therefore, a high specific capacitance requires suitable graphene-like nanosheets and pore structures.

[0107] In summary, using cotton stalks as carbon precursors has greatly improved environmental protection compared to the consumption of fossil energy; biomass cotton stalks can still retain their original structure after thermal cracking to remove degradable components, and are excellent precursors for preparing capacitor carbon. The surface of the capacitor carbon prepared by the introduction of metal magnesium in the activator has abundant graphene-like nanosheets, which provides a large specific surface area and good conductivity, and a rich pore structure, which is conducive to the contact of the electrolyte; thus providing better electrochemical performance.

[0108] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing graphene nanosheet capacitor carbon material using magnesium-assisted mixed salt, characterized in that: The following steps are involved: Step 1: Wash and dry the cotton straw raw material, place it in a tube furnace, pre-carbonize it under an argon or nitrogen atmosphere, and then crush it in a crusher to form powder; Step 2: Mix the pre-carbonized material, metal magnesium and activator in a certain mass ratio of 1:0-1:0-10; wherein the molar ratio of the activator potassium carbonate to sodium carbonate is 0:1-1:0; Step 3: placing the mixture obtained in step 2 in a tube furnace, performing an activation reaction under an argon or nitrogen atmosphere, and taking it out after cooling to room temperature; Step 4: Wash the mixture obtained in step 3 with a dilute hydrochloric acid solution and deionized water until the solution becomes neutral; Step 5: drying the product obtained in step 4 to obtain a biomass-based graphene nanosheet capacitor carbon material; Step 6: The graphene-like nanosheets obtained in step 5 are used as electrode materials.

2. The preparation method according to claim 1, characterized in that: The particle size of the cotton straw powder is less than 50 μm; the pre-carbonization temperature is 350-750°C, and the heating rate is 5-10°C min -1 , the pre-carbonization time is 3-5h.

3. The preparation method according to claim 1, characterized in that: In the step 2, the mass ratio of the pre-carbonized material to the activator is 1:1-1:10; the activators are potassium carbonate and sodium carbonate, the molar ratio of potassium carbonate to sodium carbonate is 0:1-1:0, and the mass ratio of the pre-carbonized material to metallic magnesium is 0:1-1:

0.

4. The preparation method according to claim 1, characterized in that: The activation temperature in step 3 is 600-1000°C, the activation reaction time is 5h, and the heating rate is 5°C min -1 .

5. The preparation method according to claim 1, characterized in that: In step 4, the concentration of hydrochloric acid is 0.5-2 mol / L, and the stirring time is 5-10 h.

6. A biomass capacitor carbon material, which is prepared by the method for preparing a graphene nanosheet capacitor carbon material using a metal magnesium-assisted mixed salt as described in any one of claims 1 to 5, characterized in that: The biomass capacitor carbon material includes micropores and mesopores, the micropore diameter is distributed at about 2nm, and the mesopore diameter is about 5nm; -1 At the current density, the discharge capacity is 116F g -1 .

7. A supercapacitor, characterized in that: It comprises an electrode material, wherein the electrode material is the biomass capacitor carbon material as claimed in claim 6.

8. A test method for testing the electrochemical properties of electrode materials, which is a test method for testing the biomass capacitor carbon material described in claim 6: the electrochemical performance test of the material is carried out using a three-electrode system, using 6M KOH solution as the electrolyte, a platinum electrode as the counter electrode, and saturated mercuric oxide as the reference electrode.

Citation Information

Patent Citations

  • Method for preparing three-dimensional porous graphene sheet by adopting low-temperature double-salt compound and application of three-dimensional porous graphene sheet

    CN113307254A